1991
DOI: 10.1073/pnas.88.5.1973
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacophore of debromoaplysiatoxin responsible for protein kinase C activation.

Abstract: Protein kinase C is physiologically activated by 1,2-diacyl-sn-glycerol in the S configuration. The enzyme is also powerfully activated by structurally diverse tumor promotors. A model has been developed that demonstrates how the various tumor promotors and diacylglycerols can all be accommodated by the same binding site of the kinase. One prediction of this model concerns the structural nature of the pharmacophore in the tumor promotor debromoaplysiatoxin. This prediction is realized by synthesizing the analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 17 publications
2
48
0
Order By: Relevance
“…PK-CR Binding Affinities (Ki) and log P for R-Alkylidene "Reversed Ester" Lactones (Z-and E-Isomers) fit calculated for two subgroups (Z-and E-isomers) of DAG-lactones selected from Table 1. For the R-alkylidene branched series (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), the curves revealed that affinity for PK-C reaches a maximum at ca. log P ) 6 for both Z-and E-isomers.…”
Section: Lipophilicity and Partition Coefficientsmentioning
confidence: 97%
“…PK-CR Binding Affinities (Ki) and log P for R-Alkylidene "Reversed Ester" Lactones (Z-and E-Isomers) fit calculated for two subgroups (Z-and E-isomers) of DAG-lactones selected from Table 1. For the R-alkylidene branched series (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), the curves revealed that affinity for PK-C reaches a maximum at ca. log P ) 6 for both Z-and E-isomers.…”
Section: Lipophilicity and Partition Coefficientsmentioning
confidence: 97%
“…layer was extracted with t BuOMe (4 Â 100 ml) and the combined org. phase washed with brine (200 ml), dried (MgSO 4 (7R)-7-[(1R)-1-Hydroxyethyl]-14,14-dimethyl-1,4,8-trioxacyclotetradecane-5,9-dione (9). Pd/C (10%; ca.…”
Section: (3r4r)-4-(benzyloxy)-3-{[(tert-butyl)dimethylsilyl]oxy}pentmentioning
confidence: 99%
“…50 times more active than di-O-oleoylglycerol 2 [4]. This has been ascribed to a disposition of the flexible recognition domain in a specific conformation of 1 optimal for binding to PKC.…”
mentioning
confidence: 94%
See 2 more Smart Citations